Direct CO2 hydrogenation to methane or methanol from post-combustion exhaust streams - A thermodynamic study - Carlos V. Miguel (2015)
The conversion/utilization of waste carbon dioxide is seen as a complementary option to the well-known capture, sequestration and storage strategies (CSS) to substantially reduce atmospheric CO2 (environmental concern). This approach is attractive regarding CCS strategies because CO2 can be transformed into a valuable chemical (economic benefit). Among the options available, methane and methanol are important chemicals that could be obtained from CO2 hydrogenation and used for energy production/storage or as intermediaries to other chemicals. A thermodynamic analysis regarding the hydrogenation of CO2 into CH4 or CH3OH was carried out. The analysis was performed to check the limitations and optimal conditions when converting CO2 from flue gas exhaust streams without previous removal of unnecessary species present in significant amounts (e.g. N-2, H2O and O-2). The present analysis supports that, from the thermodynamic point of view, the conversion of CO2 into CH4 is favoured in comparison to the CH3OH valorisation strategy, for the considered pressure and temperature ranges.